Regularização fundiária em reservas de desenvolvimento sustentável do Estado do Amazonas - Oliveira, Evelinn Flores De (2009)
This work had the aim of assessing the aspects concerning the regularization of land conservation units of sustainable use, in particular on sustainable development reserve of the State of Amazonas. The Amazon conservation units have several problems for effective environmental management. One of these problems is the regularization of land ownership, reaching approximately 80% of the UC 's, making it difficult to carry out environmental zoning and perform management plan. To reach this conclusion was the drive management tools, such as conservation stewardship plan, the Council Manager, the rules of procedure and so on, which facilitate the implementation of land regularization, then, to address the General aspects of land regularization and possible regulatory instruments for each category of public good and the appropriate instrument (s) by dominialidad type of conservation units. Still, we briefly land situation in the State of Amazonas, showing the law applicable to conservation units. The legal standards were exposed in the quest to understand its contents, then to establish a relationship with reality is sustainable development reserves of Amazonas. In the end, the study focused on sustainable development Reserve Tupé, located in the municipality of Manaus, listing the relevant legislation that reality, pointing the barriers that must be overcome by Tupé reserve Manager, on the steps that follow the regularization of land ownership. The problems can be classified into three groups: personal, institutional/normative and administrative. Identified that the body will have difficulties in Manager number families will benefit by land regularization because, according to the Decree Tupé reserve creation, residents (traditional) populations resident and domiciled in UC at the time of its creation. Showed high growth in the population of Tupé since the date of his name in RDS in 2005 until 2009, and part of this population fixed residence in Tupé, then the question is whether they will be included or excluded from the process of land regularization of the reservation. In the institutional field before you begin the process of settlement of RDS of Tupé, the Manager must resolve the impasse of transfer of ownership of the Union's area for the municipality of Manaus, because the RDS of Tupé was created under a federal like serfs, which has not yet been raises by the municipality. And finally, the body must solve barriers Manager created by their own legislation, ranging from legal conceptualization, lack of technical accuracy, clarity on the objectives and procedures to be followed. This, it was found that these factors contribute to the rule of law has its limited effectiveness. However, it is understood that to answer the question of social effectiveness of art. 20 of the SNUC applied to the reality of RDS of Tupé, need a trans-disciplinary study of the subject, which contains indicators of social, economic, environmental and so therefore the effectiveness of a rule of law, in particular environmental standard should not be assessed solely from the legal point of view, since this has no predetermined indicators of social effectiveness assessment of a standard and, if considered in isolation, always will be insufficient to answer these questions